Collisional formation of top-shaped asteroids and implications for the origins of Ryugu and Bennu - P. Michel (Nature Portfolio, 2020)
Asteroid shapes and hydration levels can serve as tracers of their history and origin. Here, the authors show top shape asteroids can form directly through gravitational reaccumulation and rubble piles formed in a single disruption can have similar porosities but variable degrees of hydration.